Effects of bifid triple viable capsules dissolving at intestines combined with emergency comprehensive nursing on intestinal microorganism and nutritional status of patients with coronary heart disease after percutaneous coronary intervention - Zuo, Ming; Liu, Zhi (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the combined effects of bifid triple viable capsules dissolving at intestines and emergency comprehensive nursing on intestinal microbiota, cardiovascular function, and nutritional status in coronary heart disease (CHD) patients post-percutaneous coronary intervention (PCI).Study designA randomized controlled trial.Place and duration of studyThis study was conducted at Capital Medical University from March 2023 to January 2024.MethodologyA total of 110 CHD patients who underwent PCI were randomized into two groups: the control group (CG, n = 55) receiving routine emergency nursing, and the study group (SG, n = 55) receiving emergency comprehensive nursing combined with bifid triple viable capsules (0.63 g, twice daily). Key outcomes, including left ventricular ejection fraction (LVEF), blood pressure, length of hospital stay, psychological well-being, nursing satisfaction, intestinal microbiota composition, and nutritional and lipid profiles, were measured before and after 8 weeks of intervention.ResultsThe SG demonstrated significantly higher improvements in LVEF and blood pressure and shorter hospital stays compared to the CG (p < 0.05). Psychological well-being, self-efficacy, and nursing satisfaction scores were significantly better in the SG (p < 0.05). Additionally, the SG showed greater restoration of lactobacillus and bifidobacterium levels and reduction in escherichia coli levels (p < 0.05). Nutritional markers, including hemoglobin, albumin, transferrin, and prealbumin, as well as lipid profiles, such as TG, TC, LDL-C, and HDL-C, improved significantly in the SG compared to the CG (p < 0.05).ConclusionThe combination of bifid triple viable capsules and emergency comprehensive nursing significantly improved cardiovascular function, reduced complications, enhanced self-efficacy and quality of life, and optimized intestinal microbiota and nutritional status in CHD patients after PCI.